If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = x + -1x + 1 Multiply F * x xF = x + -1x + 1 Reorder the terms: xF = 1 + x + -1x Combine like terms: x + -1x = 0 xF = 1 + 0 xF = 1 Solving xF = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by 'F'. x = F-1 Simplifying x = F-1
| 110=-9-7k | | 5x+2(32-5x)=48 | | b^2-11b=10 | | -7x+10+8x=4+x+6 | | 10y+x=4(x+y) | | p^4-10p+9=0 | | X^4-3x^3+0x^2+x-3=0 | | 12×4/5 | | 4+7=3-4 | | 22=11.1 | | 3600=20x+15y | | F(x)=1-x | | 7×2/12= | | 6z+2z=7z-5 | | -79p+6p-2p+6+42= | | 4+2(x+8)=2(2x+2)+8 | | 71x-1x=-11x+132 | | H=4.9t-4.9t^2 | | 3x(7-2)+X(4-1)+8=2 | | 71-1x=-11x+132 | | 2q-q-q+2q=14 | | 5p-p+12= | | (6x+5)-(3x^2-4x+5)= | | 7w-1=20 | | 3X+6-2X=12-2X+12 | | x+4.5=-4.5 | | 3a+2b+a+5b= | | (9p+4)=14 | | 18t+16t^2=d | | 7x^2+13x-8=0 | | 6+9x^2-2+(6+4)=x | | 4X+8+4=2X+20+8 |